2011
DOI: 10.1271/bbb.110524
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of Ethyl Vanillinin Vitroandin Vivo

Abstract: We systematically evaluated the antioxidant activity of ethyl vanillin, a vanillin analog, as compared with the activities of vanillin and other vanillin analogs using multiple assay systems. Ethyl vanillin and vanillin exerted stronger antioxidant effects than did vanillyl alcohol or vanillic acid in the oxygen radical absorbance capacity (ORAC) assay, although the antioxidant activities of vanillyl alcohol and vanillic acid were clearly superior to those of ethyl vanillin and vanillin in the three model radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 32 publications
2
34
0
Order By: Relevance
“…The order of relaxing potencies of VA and its analogs may be related to their varying hydrophobicity which, to judge from the elution time during reversed-phase high-performance liquid chromatography separation (Shyamala et al, 2007;Tai et al, 2011), follows the same ranking as observed in the present experiments. Such a difference in hydrophobicity of VA, VAA, and EtVA may be responsible not only for their different antioxidant activities/capacities (Tai et al, 2011) but also for their varying potencies in inhibiting L-type Ca 21 channels (as discussed herein), which are involved in contractions to KCl, U46619, and endothelin-1 Kasuya et al, 1989;Sato et al, 2000;Nobe and Paul, 2001).…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…The order of relaxing potencies of VA and its analogs may be related to their varying hydrophobicity which, to judge from the elution time during reversed-phase high-performance liquid chromatography separation (Shyamala et al, 2007;Tai et al, 2011), follows the same ranking as observed in the present experiments. Such a difference in hydrophobicity of VA, VAA, and EtVA may be responsible not only for their different antioxidant activities/capacities (Tai et al, 2011) but also for their varying potencies in inhibiting L-type Ca 21 channels (as discussed herein), which are involved in contractions to KCl, U46619, and endothelin-1 Kasuya et al, 1989;Sato et al, 2000;Nobe and Paul, 2001).…”
Section: Discussionsupporting
confidence: 72%
“…Based on these properties, VA, VAA, and EtVA could be used to prevent or relieve exaggerated Ca 21 influx resulting in PKC activation in coronary (Ito et al, 1994;Kadokami, et al, 1996) or cerebral (Laher and Zhang, 2001) vasospasm and other cardiovascular disorders (Khalil, 2013). However, the concentrations of VA and its analogs needed to act as antioxidants (Shyamala et al, 2007;Jung et al, 2010;Kwon et al, 2013;Lee et al, 2013) or as vasodilators (present study) are larger than the measured plasma level [0.0005 mM] reached after oral administration of 30 mg/kg VA in male ICR (imprinting control region) mice (Tai et al, 2011). This comparison implies that to obtain a therapeutically favorable coronary and/or cerebral vasodilator, larger doses of VA and its analogs would be required than are achieved with their use as additives.…”
Section: Coronary and Basilar Arterial Relaxations To Vanillinmentioning
confidence: 57%
See 2 more Smart Citations
“…Apoptosis of MCF-7 cells may be due to the DNA damage and expression of apoptotic proteins (Natarajan et al, 2011). Ethyl vanillin and vanillin exerted stronger antioxidant effects than did vanillyl alcohol or vanillic acid (Tai et al, 2011) . Rosmarinic acid has antioxidant, anti-inflammatory and antimicrobial activities.…”
Section: Resultsmentioning
confidence: 86%